Mecanismos genéticos de resistencia al tizón de la hoja (Turcicum) en el maíz tempranero de calidad con provitamina A - BELLO, Bashir Omolaran (2024)
Provitamin A quality protein maize (PVA-QPM), as a cost-effective staple maize with improved nutritional quality, has the potential to address malnutrition in rural communities in sub-Saharan Africa. The objective was to identify early maturing Turcicum leaf blight (TLB)-resistant PVA-QPM hybrids and lines with promising grain quality and yield. There are significant yield discrepancies among the selected PVA-QPM hybrids, with five hybrids - TZEIORQ 11 × TZEIORQ 20, TZEIORQ 11 × TZEIORQ 24, TZEIORQ 20 × TZEIORQ 24, TZEIORQ 22× TZEIORQ 42 and TZEIORQ 24 × TZEIORQ 42 - standing out with an average yield of 6.91 t.ha-1. The inbreds TZEQI 82 and TZEIORQ 69 exhibited notably low disease scores. The inbreds TZEIORQ 2, TZEIORQ 11, TZEIORQ 20, and TZEIORQ 70 displayed exceptional characteristics. There were significant mean squares of specific combining ability (SCA) and general combining ability (GCA) for all traits suggest that the genetic variations governing these traits are primarily influenced by additive effects. The genetic studies conducted on various traits, except TLB resistance, have indicated a positive and significant impact on GCA. There were high SCA variances for all the traits across the selected twenty-two crosses. These findings confirm that traditional breeding methods can increase maize resistance to TLB disease and develop new cultivars with high disease resistance, grain quality, and yield.